Information Literacy in TBM Pengelolaan Lingkungan Cibungur - Yanto, Andri; Anwar, Rully Khairul; Lusiana, Elnovani (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
Literacy activities as a backbone of a library or a TBM to support the literacy goal as a lifelong learner. TBM also has activities to improve the quality of life with a variety of activities undertaken so as to create self-sufficiency of citizens and improve their quality of life through a variety of information literacy activities. One TBM contributing to the improvement of the quality of life of the surrounding community is the TBM Pengelolaan Lingkungan Cibungur, Bandung Barat District, West Java, IndonesiaÂ with a variety of literacy activities. The purpose of this study was to determine how the activity of literacy in a community TBM. The research method used in this study is a qualitative case study approach. Data consists of interviews, observation and documentation. The results of this research indicate that the information literacy has run quite optimal even though the concept is not fully understood by TBM, but literacy programming in practice has been implemented with the aim of making the community in Cibungur can catch up with other regions with a wide range of activities in order to increase knowledge, skills and soft skills.